Investigation of Sacral Needle Depth in Minimally Invasive Sacrocolpopexy. Issue 4 (July 2016) - Graham, Edith; Akl, Ahmed; Brubaker, Linda; Dhaher, Yasin; Fitzgerald, Colleen; Mueller, Elizabeth Rose
Abstract : Purpose: The aims of the study were to optimize surgical safety and to minimize vertebral disc puncture during sacral needle placement at the time of minimally invasive sacrocolpopexy. Cadaveric studies report that the anterior longitudinal ligament (ALL), which covers the vertebral disc and vertebrae, has a reported thickness of only 1.4 to 2.3 mm at L5 -S1 . Intervertebral disc puncture can accelerate disc degeneration, disc herniation, and loss of disc height, a risk that may be avoidable. Materials and Methods: After institutional review board approval, research consent was obtained from women undergoing primary laparoscopic sacrocolpopexy. Intraoperatively, sacral sutures were placed in the ALL with a 1.5 cm diameter CV-2 needle using Gore-Tex suture. Depth measurements were collected using a laparoscopic ultrasound transducer positioned on the sacral promontory (SP) between the 2 ends of the needle visible through the ALL. Two still-frame US images of the single needle were taken using the BK Medical software. Needle depth was calculated by measuring the distance from the top of the ALL to the needle. Results: Two satisfactory intraoperative images were obtained for all 9 participants. The mean needle depth at the SP was 3.96 mm. The interpatient needle depth varied from 2.07 to 9.04 mm. Conclusions: In most participants (78%), the sacral needle depth exceeded 2.3 mm, suggesting that there may be risk to sacral suture placement without depth guidance at the promontory. During minimally invasive sacrocolpopexy, the depth of the ALL and the placement of the needle at the SP may result in inadvertent disc penetration. Surgeons should be conscious of the minimal depth of the ALL and consider placing the suture below the promontory to avoid the disc. Abstract : Surgeons need to be conscious of the minimal thickness of the anterior longitudinal ligament, which often lies over a disc at the sacral promontory.